Foot temperature responses during walking: a theoretical estimation of mechanical and physiological factors - Burnett, Jenna K.; Anguiano-Hernandez, Jose G.; Takahashi, Kota Z. (Frontiers in Bioengineering and Biotechnology, 2025)
Skin temperature has been previously associated with tissue complications (i.e., foot ulcers) in individuals with diabetes. Previous studies have suggested that mechanical factors during ground contact (i.e., foot shear force, foot net work), and physiological factors (i.e., skin blood flow) contribute to foot temperature changes during activities such as walking. However, it is currently unclear how mechanical and physiological factors interact to influence foot temperature. Therefore, the goal of this study was to present a framework to generate new hypotheses about the factors that drive foot temperature responses in healthy young adults during walking. This goal was accomplished in a two-part study. In the first part of the study, we collected experimental temperature data on the foot of 8 healthy young adults (1F/7M) during a 30-min walk. We then modeled the temporal response of temperature data using a linear regression and a non-linear logistic model. We reasoned that if mechanical factors alone influence the temperature responses, then the temperature would increase linearly over the walking duration (assuming similar foot mechanics from step-to-step). On the other hand, if physiological factors were at play, then the temperature would increase non-linearly over the walking duration. Experimental data indicated that the whole foot temperature increased by 3.50 ± 2.38 °C after 30 min of walking. Furthermore, the non-linear model better captured the temporal response (compared to linear model), which likely hints that both mechanics and physiology influence foot temperature. In the second part of the study, we applied a theoretical thermodynamics computation to parse the contributions of mechanical and physiological factors during walking. This computation predicted that mechanical factors accounted for 2.5 °C of the increase in foot temperature after 30 min of walking (out of the 3.5 °C), while physiological factor accounted for 1.0 °C. Furthermore, the physiological factors displayed a non-linear response during the walking duration, which were qualitatively similar to published reports of skin temperature outside the foot. Altogether, our study provides new hypotheses regarding the interaction between mechanical and physiological factors involved in foot temperature regulation, and may provide a framework to study populations at risk for foot complications due to impaired temperature regulation.